Estrogen Metabolism-Associated CYP2D6 and IL6-174G/C Polymorphisms in Schistosoma haematobium Infection - Cardoso, Rita (2017)
Schistosoma haematobium is a human blood fluke causing a chronic infection called urogenital schistosomiasis. Squamous cell carcinoma of the urinary bladder (SCC) constitutes chronic sequelae of this infection, and S. haematobium infection is accounted as a risk factor for this type of cancer. This infection is considered a neglected tropical disease and is endemic in numerous countries in Africa and the Middle East. Schistosome eggs produce catechol-estrogens. These estrogenic molecules are metabolized to active quinones that induce modifications in DNA. The cytochrome P450 (CYP) enzymes are a superfamily of mono-oxygenases involved in estrogen biosynthesis and metabolism, the generation of DNA damaging procarcinogens, and the response to anti-estrogen therapies. IL6 Interleukin-6 (IL-6) is a pleiotropic cytokine expressed in various tissues. This cytokine is largely expressed in the female urogenital tract as well as reproductive organs. Very high or very low levels of IL-6 are associated with estrogen metabolism imbalance. In the present study, we investigated the polymorphic variants in the CYP2D6 gene and the C-174G promoter polymorphism of the IL-6 gene on S. haematobium-infected children patients from Guine Bissau. CYP2D6 inactivated alleles (28.5%) and IL6G-174C (13.3%) variants were frequent in S. haematobium-infected patients when compared to previously studied healthy populations (4.5% and 0.05%, respectively). Here we discuss our recent findings on these polymorphisms and whether they can be predictive markers of schistosome infection and/or represent potential biomarkers for urogenital schistosomiasis associated bladder cancer and infertility.